2013
DOI: 10.5194/nhess-13-263-2013
|View full text |Cite
|
Sign up to set email alerts
|

Simulating future precipitation extremes in a complex Alpine catchment

Abstract: Abstract. The objectives of the present investigation are (i) to study the effects of climate change on precipitation extremes and (ii) to assess the uncertainty in the climate projections. The investigation is performed on the Lech catchment, located in the Northern Limestone Alps. In order to estimate the uncertainty in the climate projections, two statistical downscaling models as well as a number of global and regional climate models were considered. The downscaling models applied are the Expanded Downscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…The snow storage in the catchment is highly sensitive to temperature variations, which can shift the seasonal patterns of snowmelt and aquifer recharge. A similar recharge pattern that strongly depends on seasonal snow accumulation and melting has been observed in other Alpine karst systems (Finger et al, 2013;Gremaud, 2011). Previous studies suggest decreasing spring discharge with increasing temper-atures, as a result of increased evapotranspiration (e.g., Loáiciga et al, 1999).…”
Section: Hydrological Process Sensitivitiessupporting
confidence: 78%
See 1 more Smart Citation
“…The snow storage in the catchment is highly sensitive to temperature variations, which can shift the seasonal patterns of snowmelt and aquifer recharge. A similar recharge pattern that strongly depends on seasonal snow accumulation and melting has been observed in other Alpine karst systems (Finger et al, 2013;Gremaud, 2011). Previous studies suggest decreasing spring discharge with increasing temper-atures, as a result of increased evapotranspiration (e.g., Loáiciga et al, 1999).…”
Section: Hydrological Process Sensitivitiessupporting
confidence: 78%
“…Gremaud et al (2009) and Gremaud and Goldscheider (2010) studied a geologically complex, glacierized karst catchment in the Alps by combining tracer tests and hydrological monitoring and found that the changing hydro-meteorological conditions affect the water storage in snow and ice significantly, which have high impact on the aquifer recharge processes and discharge dynamics. Finger et al (2013) investigated glacier meltwater runoff in a high Alpine karst catchment under present and future climate conditions using tracer experiments, karst structure modeling and glacier melt modeling. The results indicated that parts of the glacier meltwater are drained seasonally by the underlying karst system and the expected climate change may jeopardize the water availability in the karst aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…XDS has been applied for various purposes, e.g. for early flood warning (Bürger et al, 2009), downscaling extreme precipitation projections (Dobler et al, 2013), and hydrological impact studies (Dobler et al, 2012a).…”
Section: Expanded Downscaling (Xds)mentioning
confidence: 99%
“…Climate projections indicate that a shift in snow and precipitation patterns is likely to alter catchment runoff regimes (Gobiet et al, 2014). Additionally, extreme events, such as floods and droughts, are expected to increase in frequency and intensity (Dobler et al, 2013;Rössler et al, 2012). For sustainable management of water resources in Alpine areas, it is imperative to understand the complex mountain hydrological processes (Kraller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%